Перші благодійні ініціативи родини Терещенків у Глухові. Дитячий притулок (1871–1915 рр.) - Артемова, Л.В. (Сіверщина в історії України, 2021)
У статті розглянуто перші благодійні ініціативи Терещенків
у Глухові – заснування в 1871 році дитячого притулку. У процесі
наукових пошуків встановлено, що у другій третині XIX – на початку XX ст. модернізація економічного життя та меценатська
діяльність нової української еліти – родини Терещенків – сприяла культурному відродженню та розвиткові соціально-гуманітарного простору Глухова і безпосередньо стосувалася створення останніми умов для розв’язання актуальних й пріоритетних
проблем життєдіяльності особистості й місцевої спільноти. На
основі першоджерел Центрального державного історичного архіву м. Києва (ф. 707, ф. 830) зроблено спробу заповнення існуючих
інтелектуальних прогалин сучасної історичної регіоналістики
щодо особливостей меценатської діяльності Терещенків у Глухові в означені часові межі. The article considers the first charitable initiatives of the Tereshchenkos
in Hlukhiv – the establishment of a children’s shelter in 1871. In the process
of scientific research it was found that in the second third of the XIX –
early XX centuries modernization of economic life and patronage of the new
Ukrainian elite – the Tereshchenko family-contributed to the cultural revival
and development of the social and humanitarian space of Hlukhiv and directly
related to the creation of the latter conditions for solving urgent and priority
problems of the individual and local community. On the basis of primary sources
of the Central State Historical Archive of Kyiv (f. 707, f. 830) an attempt to fill
the existing intellectual gaps of modern historical regionalism regarding the
peculiarities of Tereshchenko’s patronage in Hlukhiv within the specified time
limits was made. It was stated that influencing the intellectual development
of society and mitigating social problems in Hlukhiv, Tereshchenko, on the one
hand, contributed to the development of primary and secondary education in
the city, and on the other, in the new economic environment, «needing a huge
staff and offices of the Tereshchenko brothers» solved the problem of training
educated workers for their enterprises, on which, in many respects, depended
the further progressive development of their sugar empire.